Consumption of organic food products in Latin America: role of knowledge and emotions among women consumers. (15th December 2021) - ,
The purpose of this study is to examine the effects of knowledge and emotions among women on the consumption of organic food products. A research survey has been conducted in four supermarkets in Mexico City. In all, 276 observations were analysed in the study during the fall of 2018. Data was collected on 11 variables influencing women consumers towards developing organic products buying behaviour. The study reveals that social media updates potential women consumers on pricing, availability, quality, and in-store promotions on the organic food products. The price of organic foods plays a critical role in determining the buying behaviour of women consumers despite food safety, health consciousness, and family wellness as strong mediating factors. Proximity of outlets, quality, and family-led decision-making process builds consumption behaviour of organic products. This research contributes to the debate on organic food buying practices of women consumers in reference to health and sustainability concerns in emerging markets.